Application of Lean Six Sigma and Failure Mode and Effects Analysis (FMEA) to Reduce Waste Defects in The Paper Slitting Production Process on Release Liner at Paper Manufacturing Company - Sitanggang, Antonius Nathanael; Rusindiyanto, Rusindiyanto (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study was carried out at a paper manufacturing company that uses a two-stage production process that includes paper coating and paper slitting to create labelstock, release liner, and digital printing media. Controlling waste, particularly defects, is the issue that arose during the release liner product's paper slitting process. By calculating Defect Per Million Opportunities and Sigma Level and offering suggestions for improvement, the study seeks to determine the sigma level in the production process based on the production and defect data. According to the study's findings, the DPMO value was 1.550 at the sigma level of 4.58. Based on the Failure Mode and Effects Analysis's Risk Priority Number, the company's suggested improvement recommendations include: improving the quality of the release liner paper prior to slitting; enhancing regular material inspections and issuing supplier complaints when needed; and enhancing worker coordination and attention to detail during in-process material inspection.